A Voyage to Vardø – A Scientific Account of an Unscientific Expedition - Sterken, Christiaan; Pippin Aspaas, Per; Dunér, David; Kontler, László; Neul, Reinhard; Pekonen, Osmo; Posch, Thomas (2013)
After the “Venus Transit Conference” that took place at the University of Tromsø from June 2 to June 3, 2012, participants were given the opportunity to either stay in Tromsø until the night of June 5–6, or to participate in a voyage to Finnmark, where the historical sites Vardø, Hammerfest, and the North Cape were to be visited. This voyage culminated in the observation of the 2012 transit of Venus at Vardø. This paper gives a detailed account of this voyage that lasted from June 3 to June 6, and emphasizes the historical, scientific, philosophical, educational and cultural involvement of the participants of the voyage and of the local population. The paper concludes with reflections on the prime condition for success of any of the Venus transit expeditions of the past: the weather must cooperate in the first place – not only during the quarter of a day of the transit, but also during the preceding weeks and months in order to allow the explorers to rightly determine their geographic positions and correctly set their clocks. The latter factor is no longer an issue nowadays, but the weather aspect remains today a limiting factor as much as it was 250 years ago. Despite the variable and partly clouded weather at Vardø during the time of the transit, the participants of this expedition were able to observe Venus in front of the Sun – with interruptions due to quickly moving clouds – between 4.30 a.m. and the fourth contact at 06:53:20 a.m. A large number of impressive, partly ‘dramatic’ photographs have been taken especially in this time interval.